2016
DOI: 10.1097/jpo.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Review of Existing Brace Adherence Monitoring Methods to Assess Adherence

Abstract: Introduction Outcomes of therapeutic orthopedic brace treatments are highly dependent on adherence. Medical brace adherence studies over several years have noted the poor adherence rates among many orthopedic and orthodontic medical braces. Lack of adherence has been demonstrated in many studies to lead to unsatisfactory results. With decreased adherence, desired therapeutic effects are difficult, if not impossible to achieve, regardless of the ability of the clinical intervention. Nonadherence als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Moreover, achieving more favorable clinical outcomes requires the patient’s adherence to the use of the prescribed orthoses or prostheses. 15 , 16 The patient’s satisfaction is a factor playing a role in his/her adherence to the treatment. 17 Some researchers believe that esthetic factors and convenience, as well as economic status and social issues, affect the level of satisfaction with an orthosis or a prosthesis and can improve patients’ adherence to the orthotic/prosthetic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, achieving more favorable clinical outcomes requires the patient’s adherence to the use of the prescribed orthoses or prostheses. 15 , 16 The patient’s satisfaction is a factor playing a role in his/her adherence to the treatment. 17 Some researchers believe that esthetic factors and convenience, as well as economic status and social issues, affect the level of satisfaction with an orthosis or a prosthesis and can improve patients’ adherence to the orthotic/prosthetic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…This further emphasizes the diminished value of entrusting the treatment duration (quantity) as an effective mean of standardisation and avoiding confounding bias without a notion to the treatment adherence (quality) itself. A systematic review collated 19 studies concerned with treatment adherence to scoliosis, clubfoot, ankle, and knee immobilizer braces unanimously found inadequate adherence to all of them which ranged from 27% to 85% at best [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous studies have shown that patients stopped wearing hand orthoses as recommended due to both discomfort and the inability to perform activities of daily living [14]. Discomfort can be experienced by patients both physically, such as due to an ill-fitting orthosis, skin irritation, or sleep disturbance [14][15][16], and psychologically, such as the feeling of being different from peers and having the perception of a social stigma associated with wearing a brace [17]. Furthermore, it has been reported that psychosocial factors, such as low self-esteem, impacted compliance with treatment [17].…”
Section: Introductionmentioning
confidence: 99%